Characteristics and Managerial Capacity of Rice Farmers Impacting Family Welfare in Tangerang Banten District - Saleh, Khaerul; Wibowo, Aris Suprio; Sulaeni, Sulaeni; Bukhari, Ahmad (Kadiri University - Faculty of Agriculture, 2024)
The endeavor to enhance rice productivity in Tangerang district, nestled within the confines of Banten Province, has unfortunately not been paralleled by a corresponding improvement in the well-being of its agricultural community. Subjectively, prosperity is often perceived through the lens of familial harmony, while on an objective scale, it is defined by the fulfillment of fundamental human needs. This study sets out to meticulously examine the correlation between the characteristics of farmers and their managerial competencies on the welfare levels of farming households engaged in the cultivation of lowland rice. Specifically, the investigation is concentrated within the Sukamulya District, Tangerang Regency, Banten Province. The methodology embraced in this study is predominantly explanatory-descriptive, drawing insights from an amalgamation of primary and secondary data sources. The focal points of analysis encompass a triad of variables: farmer characteristics, managerial capacity, and farmer welfare. Leveraging Inferential Statistics, with a Structural Equation Modeling (SEM) analytical framework, the research delves into the intricate interplay between these variables. The empirical findings unearth a direct correlation between farmer characteristics and their managerial prowess. Furthermore, it underscores the consequential impact of farmer characteristics, channeled through managerial capacity, on the overall welfare of farmers. The augmentation of household welfare within farming communities predominantly hinges upon the adept management of resources, proficient business acumen, strategic planning capabilities, organizational adeptness, and adaptive resilience demonstrated by farmers and their managerial capacities.